Neuroprotection - New Approaches and Prospects 2020
DOI: 10.5772/intechopen.91028
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potentials of Natural Vitamin E for Cerebral Small Vessel Disease

Abstract: Cerebral small vessel disease (CSVD) refers to a spectrum of clinical and neuroimaging findings resulting from pathological processes of various etiologies affecting cerebral arterioles, perforating arteries, capillaries, and venules. It is the commonest neurological problem that results in significant disability, but awareness of it remains poor. It affects over half of people over 65 years old and inflicts up to third of acute strokes, over 40% of dementia, and a significant decline in physical ability in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 115 publications
(162 reference statements)
0
7
0
Order By: Relevance
“…275 These hemodynamic changes are produced by hypertension and arterial stiffness caused due to oxidative stress which arises in the cerebral vasculature and when treated with the vitamin E derivatives (alpha-tocopherol and alpha-tocotrienol), was significantly downregulated. 275 Vitamin E is a beneficial treatment for neuropathological conditions because of its ability to protect PUFA which offers neuroprotection to the brain. 22 Arachidonic acid is the major PUFA present in the central nervous system (CNS) and is metabolized by both enzymatic and nonenzymatic pathways, which produce neurotoxic metabolites.…”
Section: Nervous System Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…275 These hemodynamic changes are produced by hypertension and arterial stiffness caused due to oxidative stress which arises in the cerebral vasculature and when treated with the vitamin E derivatives (alpha-tocopherol and alpha-tocotrienol), was significantly downregulated. 275 Vitamin E is a beneficial treatment for neuropathological conditions because of its ability to protect PUFA which offers neuroprotection to the brain. 22 Arachidonic acid is the major PUFA present in the central nervous system (CNS) and is metabolized by both enzymatic and nonenzymatic pathways, which produce neurotoxic metabolites.…”
Section: Nervous System Diseasementioning
confidence: 99%
“…The cerebral small vessel disease is a hitherto unexplored neurological condition which runs a high risk for the development of several debilitating neuropathies such as ischemic stroke, dementia (up to 40% risk in older people), Alzheimer's disease, and acute physical disabilities (mostly in the over 65 ages) 275 . It occurs because of perforations in the blood vessels in the brain which is concurrent with the inability to self‐regulate the cerebral blood flow 275 .…”
Section: Tocotrienol Activity In Systemic Diseasementioning
confidence: 99%
“…66 Vitamin E. Vitamin E is a lipophilic antioxidant that works primarily against lipid peroxidation and terminates the oxidation of polyunsaturated fatty acids (PUFAs). 67 This function is critical to ensure the integrity of cellular membranes and systems that rely on the abundance of PUFAs, such as the central nervous system. 67 The vitamin E protection of PUFAs leads to neuroprotective effects under pathologic and high oxidative stress conditions.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…67 This function is critical to ensure the integrity of cellular membranes and systems that rely on the abundance of PUFAs, such as the central nervous system. 67 The vitamin E protection of PUFAs leads to neuroprotective effects under pathologic and high oxidative stress conditions. 67 Khanna et al found that vitamin E acts on key molecular checkpoints to protect against glutamateand stroke-induced neurodegeneration.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation